Stress-constrained topology optimization for material extrusion polymer additive manufacturing. Issue 3 (29th May 2021) - Liu, Jikai; Yan, Jingjing; Yu, Huangchao
Abstract: This paper presents a comprehensive numerical and experimental study on stress-constrained topology optimization for Fused Deposition Modeling (FDM) additive manufacturing. The qp method is employed to avoid the singularity issue of stress-constrained problems. The P-norm function with stability transformation is adopted to build the global stress constraint with iterative corrections to eliminate the gap between the maximum local stress and the P-norm stress. The Heaviside projection is employed to generate clear-cut 0–1 designs. Two benchmark examples have been studied with the numerical algorithm. Experiments are performed on the topologically optimized MBB beam to investigate the impact of the FDM process parameters, including deposition path direction, building direction, and slicing layer height, on the resulted structural strength. The stress-constrained designs without and with Heaviside projection are comparatively tested with experiments. The stress-minimization designs subject to different P-norm parameters are compared both numerically and experimentally. Experiments show that the deposition path direction and the building direction evidently affect the derived structural strength. Moreover, overthin structural members may severely degrade the structural strength due to manufacturing and loading uncertainties. Graphical Abstract: